CDDO and ATRA Instigate Differentiation of IMR32 Human Neuroblastoma Cells - Chaudhari, Namrata; Talwar, Priti; Lefebvre D'hellencourt, Christian; Ravanan, Palaniyandi (Frontiers in Molecular Neuroscience, 2017)
Neuroblastoma is the most common solid extra cranial tumor in infants. Improving the clinical outcome of children with aggressive tumors undergoing one of the multiple treatment options has been a major concern. Differentiating neuroblastoma cells holds promise in inducing tumor growth arrest and treating minimal residual disease. In this study, we investigated the effect of partial PPARγ agonist 2-cyano-3, 12-dioxooleana-1, 9(11)-dien-28-oic acid (CDDO) on human neuroblastoma IMR32 cells. Our results demonstrate that treatment with low concentration of CDDO and particularly in combination with all trans retinoic acid (ATRA) induced neurite outgrowth, increased the percentage of more than 2 neurites bearing cells, and decreased viability in IMR32 cells. These morphological changes were associated with an increase in expression of bonafide differentiation markers like β3-tubulin and Neuron Specific Enolase (NSE). The differentiation was accompanied by a decrease in the expression of MYCN whose amplification is known to contribute to the pathogenesis of neuroblastoma. MYCN is known to negatively regulate NMYC downstream-regulated gene 1 (NDRG1) in neuroblastomas. MYCN down-regulation induced by CDDO correlated with increased expression of NDRG1. CDDO decreased Anaplastic Lymphoma Kinase (ALK) mRNA expression without affecting its protein level, while ATRA significantly down-regulated ALK. Antagonism of PPARγ receptor by T0070907 meddled with differentiation inducing effects of CDDO as observed by stunted neurite growth, increased viability and decreased expression of differentiation markers. Our findings indicate that IMR32 differentiation induced by CDDO in combination with ATRA enhances, differentiation followed by cell death via cAMP-response-element binding protein (CREB) independent and PPARγ dependent signaling mechanisms.